Intelligent recommendation and visual detection system for crop management - Thompson, Ian (2026)
This work presents the development of an intelligent system that combines computer vision and a large language model (LLM) to assist in crop management. Its goal is to support farmers in making preventive and corrective decisions through the analysis of images and text. In the face of challenges such as climate change, pests, and resource scarcity, the tool aims to identify crops and diseases, providing accurate and accessible recommendations. The system seeks to reduce agricultural losses, improve productivity, and offer guidance in areas with limited access to experts.